Toward a new relationship between history and global mental health - Ana Antic; Gabriel Abarca-Brown; Lamia Moghnieh; Shilpi Rajpal (SSM - Mental Health, 2023)
This paper explores the relationship between historical research and the field of global mental health. It identifies a gap in the current literature, and argues that an in-depth historical approach is critical for understanding and overcoming current challenges and controversies in global mental health. The authors propose that a thick historical analysis has the capacity to broaden and diversify the discussion about the core concepts in global mental health (such as illness, suffering, care or culture), and to nuance our understanding of the field’s development and impact in specific political and social contexts. The paper analyzes how a systematic historical approach is crucial for understanding colonial and post-colonial power relations embedded in the field of global mental health, and encourages researchers and practitioners to view history as a source of imagination, and of alternative ideas and initiatives in mental health that go beyond existing psychiatric frames of representations, and towards truly radical and egalitarian projects and relations. This exercise in alternative historical imagination does not need to interfere with nor disrupt the urgency of mental health practice today; on the contrary, it is meant to improve the effectiveness of interventions. It can provide practitioners with a new and enriched language to resolve long-standing clinical dilemmas (e.g. related to patient adherence or limited success of certain cultural adaptations), which could not be properly addressed previously